Disparity in Authority of the State Administrative Court and District Court in Adjudicating Certified Land Claims - Ari, Kurniadi; Darmini Roza; Syofiarti (Ekasakti Journal of Law and Justice, 2023)
The title certificate over land is a form of State Administrative Decree, based on Article 1 number 3 of Law Number 9 of 2004 concerning the Second Amendment 2 to Law Number 5 of 1986 concerning the State Administrative Court. Related to that, if there are individuals and legal entities who object to the decision, the objection can be made through a lawsuit to the State Administrative Court based on the absolute compatibility of State Administrative Procurement. There are legal facts, the Sungai Full District Court of Jambi Province accepted, examined, tried and decided objections to the certification further in its decision stating that the certificates of the Defendants were invalid.